Pengaruh Dukungan Sosial dan Resiliensi Terhadap Subjective Well-being pada Remaja Akhir Pasca Putus Cinta di Karawang - Windi Dwi Astuti; Nuram Mubina; Rizky Ajeng Pratiwi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study examines the influence of social support and resilience on subjective well-being among late adolescents who have experienced romantic breakups in Karawang. This research employed a quantitative approach with a causal associative design. The sample consisted of 204 late adolescents aged 18–21 years in Karawang, selected using convenience sampling. Data were collected through psychological scales measuring subjective well-being, social support, and resilience, namely the Satisfaction with Life Scale (SWLS) for subjective well-being, the Multidimensional Scale of Perceived Social Support (MSPSS) for social support, and the Connor-Davidson Resilience Scale (CD-RISC) for resilience.. Instrument validity and reliability were confirmed, and data were analyzed using multiple linear regression after meeting classical assumption tests. The results showed that social support and resilience simultaneously have a significant effect on subjective well-being (F = 36.393; p < 0.05). Partially, social support (t = 4.882; p < 0.05) and resilience (t = 4.339; p < 0.05) both have positive and significant effects on subjective well-being. The coefficient of determination (R² = 0.266) indicates that 26.6% of subjective well-being is explained by these variables, while the remaining 73.4% is influenced by other factors. These findings suggest that higher social support and resilience contribute to better subjective well-being among adolescents after breakups. Thus, strengthening social relationships and internal coping capacity is essential to support adolescent mental health.